Faktor Resiko Penyebab Nyeri Punggung Bawah pada Mahasiswa Fakultas Kedokteran Universitas Muslim Indonesia (UMI) Angkatan 2021 - Ramdani, Putri; Nasaruddin, Hermiaty; Putra, Fadil Mula; Syafei, Imran; Mubarak, Andi Firman (Universitas Batanghari Jambi, 2025)
This study aims to determine the characteristics of sedentary lifestyle to complaints of low back pain in students of the Faculty of Medicine UMI class of 2021 based on age, gender, height, weight, and sleep quality. This study is a quantitative research with a cross-sectional study design. The results showed that the most complaints of low back pain were experienced by 21-year-old subjects, who were generally in the transition phase from education to the world of work. Based on gender, women experience these complaints more often than men, which are caused by biological factors such as lower muscle mass and hormonal fluctuations. Height 150-159 cm has the highest prevalence of low back pain, possibly due to less than optimal posture. College students weighing 40-49 kg also experience this complaint more often, which can be attributed to lower muscle mass. In terms of sleep quality, there was a significant relationship between sleep quality and the severity of low back pain, where respondents with low sleep quality tended to experience higher pain. Overall, this study shows a significant relationship between sedentary lifestyle and low back pain complaints in UMI Faculty of Medicine students. Further research is suggested to explore other factors such as stress, physical activity, and psychological factors that may affect sleep quality and low back pain severity